An optimisation model for the warehouse design and planning problem - Geraldes, Carla A.S. (2014)
In spite of the importance of warehouses in the field of the supply chain management, there is not a single decision model that integrates all the decisions that concerns the warehouse design and planning problem. A number of warehouse decision support models have been proposed in the literature but considerable difficulties in applying these models still remain, due to the large amount of information to be processed and to the large number of possible alternatives. In this paper we discuss a mathematical programming model aiming to support some warehouse management and inventory decisions. Our aim is to address the complexity related to the modeling of the warehouse design and planning problem. In particular a large mixed-integer nonlinear programing model (MINLP) is presented to capture the trade-offs among both inventory and warehouse costs in order to achieve global optimal design satisfying throughput requirements.